RELATIONSHIP BETWEEN LEARNING CREATIVITY, LEARNING MOTIVATION, AND SOCIAL ENVIRONMENT WITH MATHEMATICS LEARNING OUTCOMES OF CLASS XI - Oktaviani Oktaviani; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
Mathematics is one of lesson favored by students because it seems difficult to learn math. Difficulties of student learning result in a lack of learning outcomes. With the presence of a student's creative spirit, high learning motivation, and a conducive social environment are expected to improve students' mathematics learning outcomes. This study aims to determine whether there is a relationship between learning creativity, learning motivation, and social environment with mathematics learning outcomes in students class XI Science (IPA) of State Senior High School 9 Yogyakarta (SMA Negeri 9 Yogyakarta) Year of 2016/2017. The population in this research was the students of class XI IPA grade in SMA Negeri 9 Yogyakarta in the academic year of 2016/2017, consisted of class XI IPA, XI IPA II, XI IPA III, XI IPA IV, XI IPA V, totaling 148 students. Samples were taken from XI IPA III as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning creativity, learning motivation, and social environment and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between learning creativity, learning motivation, and social environment with mathematics learning outcomes in students class XI IPA of SMA Negeri 9 Yogyakarta Year of 2016/2017. It is showed by Fcount Ftable is 9,226>2,98 with R = 0,718 and R2 = 0,516 with , with RC = , RC = and RC = 57,578 , EC = , EC = and EC = .